Development of Intensity-Duration Frequency Curves for Koforidua City in Ghana - Fordjour, Alexander; F.O.A., Anyemedu; Adjei, Frank Owusu; Ibrahm, Ajani A.; Zhu, Xingye (European Scientific Journal, ESJ, 2019)
The estimation of rainfall intensity for a particular frequency is normally required for design of hydraulic and water resources engineering control structures. The main objective of this paper was to develop IDF curves for Koforidua based on recent rainfall information. Annual Maximum Rainfall depths of various durations over twenty-nine yearsfor Koforidua were obtained from the Ghana Meteorological Services in Accra. Linear regression analysis was used to make the data consistent which allowed for filling in the gaps where data were missing. The data set obtained was then subjected to frequency analysisto determine the distribution which best characterize the data set. The annual maximum series were found to be drawn from the Gumbel distribution whose parameters were computed by fitting the statistics to the data. The Kolmogorov-Smirnov test proves the appropriateness of the fitting. The trend followed the normal Rainfall Intensity-Duration-Frequency-curves. By using easy fit software, Gumbel Extreme type one was found to be the best distribution for the analysis. The results shown that for shorter durations (12 min and 24 min), the IDF Curves gave higher intensities for the same return period whiles for longer durations (42min, 1 hr, 2hr, 3hr, 6hr, 12hr and 24 hr), the IDF Curves gave low intensities for the same return period.The Intensity- Duration-Frequency-Curves obtained for the study area has a general characteristic form of Intensity-Duration-Frequency-Curves. This study could be of significance academic value and useful to improve the hydraulic and water resources engineering.